If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -8) = 40 Reorder the terms: 4(-8 + 2x) = 40 (-8 * 4 + 2x * 4) = 40 (-32 + 8x) = 40 Solving -32 + 8x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 8x = 40 + 32 Combine like terms: -32 + 32 = 0 0 + 8x = 40 + 32 8x = 40 + 32 Combine like terms: 40 + 32 = 72 8x = 72 Divide each side by '8'. x = 9 Simplifying x = 9
| -6(6x-1)=42 | | 7(x-1)=-49 | | cd=5 | | -3(x+3)=3 | | -3x^2+24x-17=0 | | -7(4+x)=7 | | 3(x-4)=42 | | 6(x-8)=12 | | -3(2-x)=12 | | log(1024)4=x | | 5x+82=9x-6 | | 3x^2+x-10=0 | | (3x+15)(x^2+10x+21)=0 | | 9-7x=123-28x | | N^2+7n+6=0 | | 2(8+x)=22 | | 12=2x^2+5x | | -3(2s-5)-15=-3(7s+5)-3 | | 2(8+1)=22 | | 5q^2+18q=8 | | k^2-3k-10=0 | | 3x+2=81 | | (-x+9)(x-5)=0 | | 16y=2 | | 10=6(a-7) | | 2x-5=7x-30 | | 3a^2x^2+2ax=7 | | -16t^2+64t+64=0 | | 6+3(x-5)=2(x-3) | | 2x^2-8x+7=0 | | -7(4x-1)+8=-28x+15 | | -7(4x-1)+8=-25x+15 |